2017
DOI: 10.3389/fncir.2017.00048
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Magnetic Stimulation Promotes Neurogenesis and Restores Cholinergic Activity in a Transgenic Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is characterized by progressive decline of memory and cognitive functions. Deep magnetic stimulation (DMS), a noninvasive and nonpharmacological brain stimulation, has been reported to alleviate stress-related cognitive impairment in neuropsychiatric disorders. Our previous study also discovered the preventive effect of DMS on cognitive decline in an AD mouse model. However, the underlying mechanism must be explored further. In this study, we investigated the effect of DMS on spatial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 29 publications
2
18
1
Order By: Relevance
“…The 5XFAD model allows for an accelerated timetable of cognitive dysfunction associated with Aβ-related AD pathology in comparison to the Tg2576 model [34,35] which was used in our prior studies. 5XFAD mice show impaired remote memory stabilization prior to four months of age [49]; impaired spatial memory in the Y-maze at 4-5 months of age [35], Morris water maze at six months of age [50,51], and radial water maze at eight months of age [52]; decreased working memory and learning during NORT testing at six months of age [50]; and decreased contextual fear memory by six months of age [38,49,53]. We tested object recall (NORT) and contextual fear (CFR) memory of approximately 8-9 month old female and male 5XFAD mice and WT littermates treated with CAW for 3-4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The 5XFAD model allows for an accelerated timetable of cognitive dysfunction associated with Aβ-related AD pathology in comparison to the Tg2576 model [34,35] which was used in our prior studies. 5XFAD mice show impaired remote memory stabilization prior to four months of age [49]; impaired spatial memory in the Y-maze at 4-5 months of age [35], Morris water maze at six months of age [50,51], and radial water maze at eight months of age [52]; decreased working memory and learning during NORT testing at six months of age [50]; and decreased contextual fear memory by six months of age [38,49,53]. We tested object recall (NORT) and contextual fear (CFR) memory of approximately 8-9 month old female and male 5XFAD mice and WT littermates treated with CAW for 3-4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that hCRY2 senses magnetic field ( 8 ). Magnetic field can be manipulated in clinical practice through transcranial magnetic stimulation, which interestingly increases neurogenesis ( 38 ). Perhaps transcranial magnetic stimulation improves neurologic outcome in a series of neuropsychiatric diseases through stimulation of hCRY expression and consequent neurogenesis.…”
Section: Potential Implications Of the Hypothesismentioning
confidence: 99%
“…More recently, biophysical factors have been suggested to induce neurogenesis. Those include ultrasound, magnetic, and deep brain electrical stimulation [25][26][27][28][29][30][31][32][33]. Ultrasound stimulation is non-invasive and can induce hippocampal neurogenesis in healthy mice [29].…”
Section: Introductionmentioning
confidence: 99%